Self-organizing joint sensing and power allocation scheme (SJSPA) to coordinate cross-tier interference for LTE-A heterogeneous networks - Hasan, Mohammad Kamrul; Ismail, Ahmad Fadzil; Hassan Abdalla Hashim, Aisha; Abdullah, Khaizuran; Mohd. Ramli, Huda Adibah; Islam, Shayla; Badron, Khairayu (Institute of Electrical and Electronics Engineers Inc., 2014)
Heterogeneous Networks (HetNet) are composed of multi-mode, multi-layer, and multi-band network structures and utilize cells of varying sizes. To cover large areas, established base stations (macro sites) are used; for coating buildings, microcells(macro-eNBs) are employed; for covering individual levels or floors in a building, Pico-cells are utilized; and finally for extending wireless coverage to individual apartments, small offices, and home based businesses, femtocells (HeNodeB) are exploited. The goal behind the implementation of HetNet involves incrementing the capacity, modifying spectrum use, lowering the capital and operating costs, as well as offering steady user-based experience of network architecture. However, these random HeNodeB deployments raises co-tier and cross-tier interference which results system performance degradation. In this paper, therefore, to coordinate the cross-tier interferences a SJSPA scheme will be proposed using the joint sensing and power control algorithm. The proposed SJSPA is mainly for cross-tier interference coordination scheme for uplink communication.The proposed scheme is simulated by Monte Carlo simulation which demonstrates that the scheme efficiently reimburses cross-tier interference, and provides better macro-eNB as well as HeNodeB throughput compare with conventional power control techniques.